The standard theory of economic behavior towards risk large risks versus small risks - Ooi, Ai Yee; Mohd Fahmi Ghazali (Institute of Interdisciplinary Business Research, 2011)
This paper focuses on some of the major theories of economic behavior towards risks and its efficiency in explaining risk attitudes towards large risks and small risks alike. Risk attitude measures the willingness of a decision maker to undertake risks in return for perceived rewards, ranging from risk aversion, risk neutrality, to risk preference. Due to earlier research exposing the limitations of the expected utility theorem in plausibly explaining risk aversion over relatively smaller stakes, this paper has empirically explored the possibilities that may cause similar ambiguous explanations in such modest-scale risk aversion. The empirical examination of the expected utility theory generally lends further supportive evidence that only large risks are capable of explaining risk aversion, with small to moderate risks being incapable of explaining risk-aversive behavior. Many other risk theories remain to be explored, and it is hoped that variants of these risk models might eventually lead to a more comprehensive coverage of risk behavior over the spectrum of large to small risks.